Interaction of COMT rs4680 and BDNF rs6265 polymorphisms on functional connectivity density of the left frontal eye field in healthy young adults - Li, Wei (Hum Brain Mapp, 2016)
As modulators of dopamine availability and release in the brain, COMT and BDNF polymorphisms have demonstrated interactions on human cognition; however, the underlying neural mechanisms remain largely unknown. In this study, we aimed to investigate the interactions of COMT rs4680 and BDNF rs6265 on global functional connectivity density (gFCD) of the brain in 265 healthy young subjects. We found a significant COMT × BDNF interaction on the gFCD in the left frontal eye field (FEF), showing an inverted U‐shape modulation by the presumed dopamine signaling. This finding was consistently repeated in the gFCD analyses using other four connection thresholds. Our findings reveal a COMT × BDNF interaction on the FCD in the left FEF, which may be helpful for understanding the neural mechanisms of the COMT × BDNF interactions on the FEF‐related cognitive functions. Hum Brain Mapp 37:2468–2478, 2016. © 2016 Wiley Periodicals, Inc.